2008
DOI: 10.1111/j.1537-2995.2007.01589.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial comparing immediate versus delayed clamping of the umbilical cord in preterm infants: short‐term clinical and laboratory endpoints

Abstract: Background-Most neonates less than 1.0 kg birth weight need red blood cell (RBC) transfusions. Delayed clamping of the umbilical cord 1 minute after delivery transfuses the neonate with autologous placental blood to expand blood volume and provide 60 percent more RBCs than after immediate clamping. This study compared hematologic and clinical effects of delayed versus immediate cord clamping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(88 citation statements)
references
References 21 publications
3
84
0
1
Order By: Relevance
“…[25][26][27][28][29][30][31][32][33][34][35] For the critical outcome of severe IVH, we identified very-low-quality evidence (downgraded for imprecision and very high risk of bias) from 5 randomized clinical trials enrolling 265 patients showing no benefit to delayed cord clamping (OR, 0.85; 95% CI, 0.20-3.69). 26,27,31,32 For the critical outcome of periventricular hemorrhage (PVH)/IVH, we identified very-low-quality evidence (downgraded for imprecision and very high risk of bias) from 9 randomized clinical trials enrolling 499 patients showing benefit of delayed cord clamping (OR, 0.49; 95% CI, 0.29-0.82).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…[25][26][27][28][29][30][31][32][33][34][35] For the critical outcome of severe IVH, we identified very-low-quality evidence (downgraded for imprecision and very high risk of bias) from 5 randomized clinical trials enrolling 265 patients showing no benefit to delayed cord clamping (OR, 0.85; 95% CI, 0.20-3.69). 26,27,31,32 For the critical outcome of periventricular hemorrhage (PVH)/IVH, we identified very-low-quality evidence (downgraded for imprecision and very high risk of bias) from 9 randomized clinical trials enrolling 499 patients showing benefit of delayed cord clamping (OR, 0.49; 95% CI, 0.29-0.82).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…In a study on infants with gestational age less than 36 weeks in two groups of immediate and delayed clamping, Strauss et al (2008) reported a significant increase in circulating RBC volume/mass (P = 0.04) and weekly hematocrit (P < 0.005). In that study, the need for mechanical ventilation did not differ between the two groups, and the need for phototherapy was higher in the delayed group (7). No case of seizure was observed in the delayed clamping group.…”
Section: Discussionmentioning
confidence: 68%
“…29 Preterm infants (30-36 weeks' gestation at birth) randomized to delayed cord clamping (at 1 minute of age) had larger circulating red blood cell (RBC) volume, no difference in hematocrit at birth, but higher hematocrit at 7, 14, 21, and 28 days of age compared with preterm infants randomized to immediate cord clamping within 5 seconds of birth. 30,31 There was no increase in polycythemia or jaundice in the delayed cord clamping groups. 31 Another randomized controlled trial found that preterm infants assigned to delayed cord clamping (30-90 seconds after birth) had significantly higher blood volumes regardless of mode of delivery (cesarean section or vaginal delivery) compared with infants who had immediate cord clamping.…”
Section: Preterm Infantsmentioning
confidence: 98%
“…30,31 There was no increase in polycythemia or jaundice in the delayed cord clamping groups. 31 Another randomized controlled trial found that preterm infants assigned to delayed cord clamping (30-90 seconds after birth) had significantly higher blood volumes regardless of mode of delivery (cesarean section or vaginal delivery) compared with infants who had immediate cord clamping. 32 Kinmond and colleagues reported that preterm infants randomized to "regulated" cord clamping (delay for 30 seconds with the infant held below the introitus) had higher hematocrits without polycythemia, a lower requirement for blood transfusion, and spent less time on supplemental oxygen compared with preterm infants assigned to "random" cord clamping (within 10 seconds of birth and not held below the introitus).…”
Section: Preterm Infantsmentioning
confidence: 98%
See 1 more Smart Citation